Antagonistic effects of smoking and maternal glycemia on fetal growth: a retrospective study among 13,958 pregnant French women - Cosson, Emmanuel; Carbillon, Lionel; Tatulashvili, Sopio; Bihan, Hélène; Vicaut, Eric; Barka, Ines; Pinto, Sara; Rezgani, Imen; Zerguine, Mohamed; Portal, Jean-Jacques; Fermaut, Marion; Puder, Jardena J.; et al. (Frontiers in Endocrinology, 2025)
IntroductionSmoking and hyperglycemia first diagnosed during pregnancy (H1inP) have opposing effects on fetal growth. The aim of this study was to explore adverse pregnancy outcomes, particularly fetal growth, according to the smoking and H1inP status.MethodsWe included 13,958 women from a large French dataset (2012–2018). Using multivariable regression analyses, we retrospectively evaluated the risk of large-for-gestational-age (LGA) babies and other adverse outcomes according to the H1inP and smoking status in four groups: no H1inP/non-smoker (group A: n = 10,454, 88.2%), no H1inP/smoker (group B: n = 819, 5.9%), H1inP/non-smoker (group C: n = 2,570, 18.4%), and H1inP/smoker (group D: n = 115, 0.8%).ResultsThe rates of LGA were 8.9%, 4.0%, 14.6%, and 8.7% in groups A, B, C, and D, respectively (global ANOVA p < 0.0001, factor H1inP p = 0.0003, factor smoking p = 0.0002, and interaction p = 0.48). After adjustment for potential confounders including age, body mass index, employment, ethnicity, parity, hypertension before pregnancy, gestational weight gain, and alcohol and drug consumption, H1inP was associated with a higher risk [odds ratio (OR) = 1.50, 95% confidence interval (95%CI) = 1.30–1.74] and smoking with a lower risk (OR = 0.35, 95%CI = 0.25–0.50) of LGA. In addition, H1inP was associated with a lower total gestational weight gain and a lower rate of small-for-gestational-age (SGA) babies, but higher rates of hypertensive disorders and more frequent caesarean sections and admissions in the neonatal intensive care unit. Smoking was associated with higher rates of SGA, including severe SGA (<3rd centile), and this despite a higher total gestational weight gain. Smoking increased the risk of hypertensive disorders only in women with H1inP.DiscussionSmoking among women with H1inP could mask the risk of maternal hyperglycemia for LGA babies. This could provide a false sense of security for women with H1inP who smoke, particularly when assessing for LGA alone, but these women still face other risks to their health, such as hypertensive disorders and the health of the fetus.